Effects of Vacancy Concentration and Temperature on Mechanical Properties of Single-Crystal γ-TiAl Based on Molecular Dynamics Simulation - Ruicheng Feng; Hui Cao; Haiyan Li; Zhiyuan Rui; Changfeng Yan (High Temperature Materials and Processes, 2018)
Molecular dynamics simulation is used to analyze tensile strength and elastic modulus under different temperatures and vacancy concentrations. The effects of temperature and vacancy concentration on the mechanical properties of γ-TiAl alloy are investigated. The results show that the ultimate stress, ultimate strain and elastic modulus decrease nonlinearly with increasing temperature and vacancy concentration. As the temperature increases, the plastic of material is reinforced. The influence of temperature on strength and elastic modulus is larger than that of vacancy concentration. The evolution process of vacancy could be observed clearly. Furthermore, vacancies with different concentrations develop into voids first as a function of external forces or other factors, micro cracks evolve from those voids, those micro cracks then converge to a macro crack, and fracture will finally occur. The vacancy evolution process cannot be observed clearly owing to the thermal motion of atoms at high temperature. In addition, potential energy is affected by both temperature and vacancy concentration.